Dayananda's outline of Vedic philosophy - Prakash, Satya, 1905- (Dayanand Sansthan, 1975)
Interpretive study of the philosophy of Swami Dayananda Sarasvati, 1824-1883, founder of Arya Samaj, Hindu reform movement.